Corporate Social Responsibility Legal Framework in Southeast Asia: Comparing Indonesia, Malaysia, and Thailand - Anggusti, Martono; Dewi Siregar, Fitri Yanni; Chansrakaeo, Ruetaitip (SASI, 2025)
Introduction: Corporate Social Responsibility (CSR) has evolved over time, reflecting changes in corporate thinking and practices regarding their relationships with society and the environment.Purposes of the Research: This research aims to analyze the regulation and implementation of CSR in Indonesia to compare it with CSR regulations in other Southeast Asian countries, namely Malaysia and Thailand.Methods of the Research: This research is a normative legal study that emphasizes a conceptual and legislative approach.Results of the Research: The development of the concept of CSR began in the 18th century by Robert Owen, who provided facilities for employees. CSR rapidly evolved in the 20th century, with large companies in the US establishing social departments. Milton Friedman's thinking about profit as the primary goal of business and John Elkington's concept of the "triple bottom line" also influenced the development of CSR. CSR functions as the moral responsibility of companies towards society and the environment, implemented through transparency, ethics, and responsible business decisions. In Indonesia, CSR has been regulated by law since 2007, with the aim of improving the quality of life and supporting sustainable development. A comparison of CSR regulations in Indonesia, Malaysia, and Thailand shows that although their goals are similar, namely to encourage corporate contributions to social and environmental development, their approaches differ. Indonesia implements strict legal obligations, Malaysia combines voluntary elements with supportive regulations, while Thailand prioritizes a cultural and voluntary approach with government recognition. Thailand is recognized as the best example in the implementation of CSR in ASEAN, with a higher quality of implementation compared to other countries.